Aldehyde dehydrogenase 2 partly mediates hypotensive effect of nitrite on l-NAME-induced hypertension in normoxic rat. (October 2014) - Sonoda, Kunihiro; Ohtake, Kazuo; Kubo, Yoshinori; Uchida, Hiroyuki; Uchida, Masaki; Natsume, Hideshi; Kobayashi, Miya; Kobayashi, Jun
Abstract Nitrite has become a topic of interest in the field of medical research because of its potential therapeutic role as an alternative source of nitric oxide (NO). While the bioconversion of nitrite to NO occurs via either nonenzymatic or enzymatic reduction under acidic or hypoxic conditions, little is known about its conversion to NO under normoxic conditions. Because of a recent report of aldehyde dehydrogenase 2 (ALDH2)-catalyzed glyceryl trinitrate (GTN) vasorelaxation by denitration of GTN to 1, 2-glyceryl dinitrate (1, 2-GDN) and nitrite, we therefore investigated a catalytic activity of ALDH2 for nitrite reduction and subsequent effect on Nω-nitro-l-arginine methyl ester (l-NAME)-induced hypertension in normoxic rat. Male Sprague–Dawley rats treated with l-NAME in drinking water for 3 weeks developed hypertension with significantly reduced plasma levels of nitrite and nitrate. The intravenous injection of sodium nitrite lowered the arterial pressure in a dose-dependent manner (17, 50 and 150 μmol/kg). Pretreatment with ALDH2 inhibitors (cyanamide and chloral hydrate) partially inhibited the hypotensive responses to sodium nitrite. In addition, cyanamide significantly delayed the nitrite clearance from plasma and most of the organs examined during the experimental period. These results suggest that ALDH2 may be at least in part involved in nitrite-mediated hypotensive effects and nitrite catalysis in many organs of normoxic rats.